"MaddAddam Trilogy" as a Historical Chronicle of the Silenced in a (Dystopian) Society - Ćuk, Maja; Panajotović, Artea (Collection of Papers of the Faculty of Philosophy in Priština, 2020)
The MaddAddam Trilogy includes three novels written in the form of speculative fiction. The narrators and major protagonists in the first two works, Oryx and Crake and The Year of the Flood, are human survivors after the pandemic that has obliterated almost all population on the planet. In these symbolic cautionary tales that reflect current cultural and economic conditions, Margaret Atwood makes readers think about the questions what if mankind was completely eradicated and what if the construction of a new species could be masterminded successfully. In the third book of the trilogy, MaddAddam, the apocalyptic story is retold by one of the genetically engineered beings, whose account provides a glimmer of hope for the future. The aim of this paper is to analyse the roles of the narrators and characters in the aforementioned works (Snowman, Toby, Ren, Adam One and Blackbeard) as recorders of the circumstances before, during and after the tragic event, by relying on Hayden White’s theoretical views on the making of historical narratives.
Keywords: Margaret Atwood; apocalyptic narratives; emplotment; Oryx and Crake; The Year of the Flood; MaddAddam